A Link between Autophagy and the Pathophysiology of LRRK2 in Parkinson's Disease - Patricia Gómez-Suaga; Elena Fdez; Marian Blanca Ramírez; Sabine Hilfiker (Parkinson's Disease)
Parkinson's disease is a debilitating neurodegenerative disorder, and its molecular etiopathogenesis remains poorly understood. The discovery of monogenic forms has significantly advanced our understanding of the molecular mechanisms underlying PD, as it allows generation of cellular and animal models carrying the mutant gene to define pathological pathways. Mutations in leucine-rich repeat kinase 2 (LRRK2) cause dominantly inherited PD, and variations increase risk, indicating that LRRK2 is an important player in both genetic and sporadic forms of the disease. G2019S, the most prominent pathogenic mutation, maps to the kinase domain and enhances enzymatic activity of LRRK2, which in turn seems to correlate with cytotoxicity. Since kinases are druggable targets, this has raised great hopes that disease-modifying therapies may be developed around modifying LRRK2 enzymatic activity. Apart from cytotoxicity, changes in autophagy have been consistently reported in the context of G2019S mutant LRRK2. Here, we will discuss current knowledge about mechanism(s) by which mutant LRRK2 may regulate autophagy, which highlights additional putative therapeutic targets.